2020
DOI: 10.1002/spe.2866
|View full text |Cite
|
Sign up to set email alerts
|

Data fusion analysis for attention‐deficit hyperactivity disorder emotion recognition with thermal image and Internet of Things devices

Abstract: Summary Attention‐deficit hyperactivity disorder (ADHD) is a symptom of behavioral or emotional problems as these problems affect children's learning and social integration. With the advancements in the Internet of Things (IoTs), emotions can be detected through image and physiological data. However, some critical ADHD children are often accompanied by the inability to control their body and even facial expressions, making emotion recognition technologies difficult to develop successfully. This study aims to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…The advent and advancement of robotics have enabled the development of tasks that humans cannot perform, or at least not with such precision [66][67][68]. In the field of eHealth, robotics has played a fundamental role in helping and treating people with various neurological conditions such as trauma [69], dementia [33][34][35][36][37], ASD [24][25][26][27][28], cerebral palsy [29][30][31][32] and ADHD [18][19][20][21][22][23]. Although in recent years the application of robotics in the treatment and support of ADHD has received considerable research attention, however, it is far inferior compared to dementia, autism, and cerebral palsy.…”
Section: Evolution Of Robotic Application In Adhd Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The advent and advancement of robotics have enabled the development of tasks that humans cannot perform, or at least not with such precision [66][67][68]. In the field of eHealth, robotics has played a fundamental role in helping and treating people with various neurological conditions such as trauma [69], dementia [33][34][35][36][37], ASD [24][25][26][27][28], cerebral palsy [29][30][31][32] and ADHD [18][19][20][21][22][23]. Although in recent years the application of robotics in the treatment and support of ADHD has received considerable research attention, however, it is far inferior compared to dementia, autism, and cerebral palsy.…”
Section: Evolution Of Robotic Application In Adhd Treatmentmentioning
confidence: 99%
“…The associated consequences of ADHD are behavioral and emotional problems that affect learning and social integration. The study [23] has found that emotions can be detected through processing of physiological and image data. However, some children with critical ADHD are often accompanied by the inability to control their facial expressions, making it difficult to recognize the emotion.…”
Section: Improvement Of Traditional Therapeutic Sessionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Visual recognition lays the foundation for artificial intelligence science and is crucial for various applications, including space exploration, , smart vehicles, internet of things, advanced manufacturing, , and others. Visual recognition technology mainly depends on the optical information collection, as well as further process and analysis through visual processing algorithms to acquire symbolic descriptions of the scenes, thereby identifying the objects or environments. However, aimed objects might exist in light-interference or dark environments, such as smoke fogs, caves, muddy water, or other surroundings that greatly disturb the collection of optical information.…”
Section: Introductionmentioning
confidence: 99%